Effect of Fluid-Structure Interaction on Noise Generation in MAV with Fixed and Flapping Membrane Wing - S. Syam Narayanan (Isfahan University of Technology, 2021)
An experimental study on the effect of fluid-structure interaction on noise generation in Micro Air Vehicle (MAV) with fixed and flapping membrane Tipula sp. wing is investigated. The acoustic performance of the fixed and flapping wing which made up of certain characteristic thin materials such as Low-density Polyethylene Terephthalate (PET), Thin Aluminium sheets (Al), and Non-woven fabrics (NWF) is analysed. An acoustic study is conducted to estimate the acoustic characteristic parameters of the insect mimic- membrane wing for various flapping conditions with various flapping frequency. In this research, the membrane wing with15cm of the total span is tested on both fixed and flapping MAV at different flexibility conditions and velocity conditions. The study of flapping MAV enables the study of the characteristic effects of sound emitted during the flapping motion of a wing. With the analysed results, the performance of wings is identified and compared with the sound pressure level. After analysing different materials, it is found that NWF produces 20% less noise than the other two more materials. Since the stiffness to strength ratio of metal is high, the formation of vortices is less compared to other membranes. For all fixed membrane wings at low Strouhal numbers, the formation of vortices is very low, and when the Strouhal number increases, the vortices became dense and results in the reduction of Sound pressure level.